Implementation of Risk Management In PT AXA Financial Indonesia Health Insurance Products - Dewi, Mariana Puspa; Wiyarni, Wiyarni (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2025)
The background of importance of risk in the insurance industry is to manage and transfer risk from individuals or groups to insurance companies. In health insurance, the main risk is unexpected medical care costs, which can burden the finances of individuals and insurance companies if not appropriately managed. The purpose of this research is to find out how risk management is implemented in insurance companies, especially AXA Financial Indonesia, what the underwriting process is in accepting and rejecting potential health insurance participants, and how PT AXA Financial Indonesia mitigates (manages) risks. The method used in this research is descriptive qualitative. This study uses several data collection methods, namely: In-Depth Interviews with Underwriters in Insurance Companies, Actuaries who handle risk analysis, and customers as users of insurance services. The interview technique uses open-ended questions to explore deeper insights and other research methods are document and policy analysis in the form of Government Regulations on Health Insurance and Internal Guidelines of Insurance Companies regarding underwriting procedures, claims management, and re-insurance strategies. This research uses the case study method because this method is more suitable if the main research question is how or why, and the focus of the research is on contemporary or current phenomena. This type is a form of research that aims to describe events that occur naturally or are man-made. The results of the research are that PT AXA Financial Indonesia has implemented risk management in its business management.